[Bis(3,5-dimethylpyrazol-1-yl)methane]{N-[1-(2-oxidophenyl)ethylidene]-dl-alaninato}copper(II) monohydrate - Zhao, Gan-Qing (International Union of Crystallography, 2008)
In the title compound, [Cu(C(11)H(11)NO(3))(C(11)H(16)N(4))]·H(2)O, the Cu(II) atom is five-coordinate in a distorted square-pyramidal geometry. The basal positions are occupied by three donor atoms from the tridentate Schiff base ligand and by one N atom from a bis(3,5-dimethylprazol-l-yl)methane ligand. The apical position is occupied by the N atom of the other ligand of this type. There are only van der Waals contacts in the crystal structure.